The use of specialised Sheff-Vax ACF supplements for ВНК-21/SUSP/ARRIAH cell cultivation and FMDV reproduction - M. S. Guseva; M. I. Doronin; A. A. Shishkova; D. V. Mikhalishin; M. A. Shevchenko; B. L. Manin (Ветеринария сегодня)
Compliance with the existing purity and safety requirements for immunobiologicals can be effectively achieved by the use of serum-free nutrient media and specialised supplements of non-animal origin. The paper shows the possibility of using Sheff-Vax ACF® supplements (Kerry, Inc., Ireland) for ВНК-21/SUSP/ARRIAH cell cultivation and FMDV reproduction. By passage 7, cell concentration and growth rate with Sheff-Vax Plus PF ACF were found to be 40–60% higher than with Sheff- Vax PF ACF and Sheff-Vax Plus ACF. No differences were observed as regards changes in pH. During FMDV reproduction in the cells, it was found that the number of 146+75S components in the test samples containing 1 million cells was 2.3–2.4 higher compared to the controls. Cells cultured with the use of Sheff-Vax Plus PF ACF supplement had normal morphology and multiple dynamic protrusions. In the presence of this supplement, growth rate and suspension concentration in the test and control samples became equal by passage 7. The number of immunogenic components of FMDV reproduced in the cells grown using Sheff-Vax Plus PF ACF was 20–30% higher than in the cells grown using other supplements. ВНК-21/SUSP/ARRIAH cell concentration and growth rate in the presence of specialised supplements were found to be lower than those in the control samples with serum and blood protein hydrolysate added to the nutrient medium. The virus yield from 1 million cells was higher in the culture grown using Sheff-Vax ACF supplements. Sheff-Vax Plus PF ACF was found to be the most suitable for ВНК-21/SUSP/ARRIAH cell cultivation and FMDV reproduction in the said cells out of the three tested supplements.